2009
DOI: 10.1007/s10597-009-9182-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Interventions for Patients Presenting to the Psychiatric Emergency Service (PES) with Major Mental Illnesses and At-risk Drinking

Abstract: The presentation for care in psychiatric emergency setting provides an opportunity to assist individuals with mental health disorders and problems related to alcohol use. The purpose of this pilot study was to determine whether clinician-administered brief alcohol interventions are effective in reducing alcohol consumption in patients who screen positive for at-risk drinking in the psychiatric emergency setting. A total of 390 PES patients were screened; 87 (schizophrenia/bipolar disorder, n = 34; depression/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…2007), drinking days (Graeber et al . 2003), drinks per week (Milner et al . 2010), alcohol use per month (Herman et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2007), drinking days (Graeber et al . 2003), drinks per week (Milner et al . 2010), alcohol use per month (Herman et al .…”
Section: Resultsmentioning
confidence: 99%
“…2000), concurrent drug and alcohol misuse (Archie et al . 2007), and binge drinking (Milner et al . 2010) were observed, along with increases in abstinence from alcohol (Graeber et al .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the PES, as a front-line system in mental health care delivery, is called upon to assess and, increasingly, to treat a very broad range of psychopathology. 25 , 26 This broad range in itself would tend to dilute the importance of any one diagnostic category. Third, diagnostic stability may be a possible limiting factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(It should be noted, however, that each was based on patient samples of ≤30 people.) Finally, two additional studies explored the feasibility of interventions for alcohol misuse among people with mental illness, the first testing the efficacy of SBIRT among patients presenting to a psychiatric emergency service [19] and the second examining the efficacy of BI conducted by telephone among psychiatric outpatients [20]. Although neither study employed a comparison group, both reported reduced alcohol consumption at six-month follow-up.…”
Section: Introductionmentioning
confidence: 99%